MENGEMBANGKAN STRATEGI BISNIS DI ERA TRANSFORMASI DIGITAL - Annisa Afwani; Khaila Calsa Fhadillah; Muhammad Habib Rifky; Nurbaiti (CV. Barokah Publsiher, 2025)
Digital transformation has fundamentally changed the way companies operate, interact with customers, and compete in global markets. Companies are not only faced with the need to adopt new technology, but also have to adapt their business models, internal processes and human resource management strategies to remain relevant. This research aims to explore effective business strategies in facing the era of digital transformation. The research method used is qualitative, with a case study approach and in-depth interviews with companies that have implemented digital transformation. Research findings show that technology integration, business model innovation, development of HR capabilities, and the formation of an adaptive organizational culture are key factors for success. This research concludes that a comprehensive and holistic business strategy—combining aspects of technology, people, processes and business models—is the main key to building a competitive company in the digital era.